Long-term Radiographic Outcome of Occipitocervical Fixation: An Analysis of Fusion Rate and Spontaneous Subaxial Alignment Change at an Average 7-year Follow-up. Issue 3 (1st February 2021) - Shimizu, Takayoshi; Fujibayashi, Shunsuke; Otsuki, Bungo; Takemoto, Mitsuru; Murata, Koichi; Matsuda, Shuichi
Abstract : Study Design: Retrospective case series Objective: The aim of this study was to investigate the long-term radiographic outcome of patients who underwent occipitocervical fixation (OCF) using a modern screw/rod system. Summary of Background Data: Few studies have reported fusion rates and radiographic alignment changes in unfused subaxial segments after OCF at a long-term follow-up. Methods: We retrospectively reviewed 22 patients who underwent OCF with a modern screw-based construct. The patients satisfied the minimum 2-year radiographic follow-up. Baseline demographics and the following pre- and postoperative sagittal alignment parameters were investigated. McGregor slope, O-C2 angle (OC2A), and C2-7 Cobb angle (CL). We grouped patients into those whose OC2A increased postoperatively (OC2A-increase group) and those whose OC2A decreased postoperatively (OC2A-decrease group). The postoperative sagittal alignment change was compared between the 2 groups at the final follow-up. The perioperative complications as well as fusion status based on computed tomography (CT) were investigated. Results: The average follow-up period was 89.7 months. The lowest instrumented vertebra was at C2 (63.6%), C3 (18.1%), or C4 (18.1%). The fusion rate at the final follow-up was 77.2%. Postoperative dysphasia occurred in two patients (16.6%) in the OC2A-decrease group, whereas distal junctional kyphosis was observed in two patients (20.0%) in the OC2A-increase group. The OC2A-increase group demonstrated a mean 4.8° decrease in CL as a compensation for the 5.1° increase in OC2A. In contrast, the OC2A-decrease group showed a mean 9.2° increase in CL as a compensation for the 6.3° decrease in OC2A. Conclusion: The CT-confirmed fusion rate of OCF was 77.2% over an average 89.7-month follow-up. Compensatory sagittal alignment change can occur in the unfused subaxial segments in conjunction with the alignment change in the instrumented OC segments, whereas the horizontal gaze was maintained. Strong consideration for the intraoperative measurement of the OC2A should be given during OCF to minimize both early and long-term complications. Level of Evidence: 4 Abstract : The computed tomography (CT)-confirmed fusion rate of occipitocervical (OC) fixation was 77.2% over an average 89.7-month follow-up. Compensatory sagittal alignment change can occur in the unfused subaxial segments in conjunction with the alignment change in the instrumented OC segments, whereas the horizontal gaze was maintained.